(untitled) (Scottish Historical and Archaeological Internet Reports, 2008)
This section considers the general properties of quartz, formation of quartz sources, general geological provenance and the varieties of quartz encountered in Scottish lithic assemblages according to geological classifications (rock crystal, milky quartz, very fine-grained or ’greasy’ quartz, quite fine-grained quartz and coarse-grained quartz).